Evaluation of anti-epithelial-mesenchymal transition property of Garcinia mangostana rind extract - Suganthi Muralidharan; Adaikkalam Vellaichamy (SpringerOpen, 2021)
Abstract Background Epithelial-mesenchymal transition (EMT) helps solid tumors to lose their intercellular adhesive property and drives metastasis. As mangosteen fruit is known for many beneficial effects including antimicrobial, antioxidant, and anti-tumorigenic properties and has been used widely in traditional medicine, we interrogated its possible anti-metastatic effect on MCF-7 breast cancer cells. Results We found that aqueous mangosteen rind extract (MRE) inhibited growth of MCF-7 and altered the transcript levels of ERα, ERβ, and EGFR genes. Additionally, the MRE changed the expression of important markers of EMT, E-Cadherin, N-Cadherin, Snail, and MMP-9. Moreover, MRE inhibited migration of MCF-7 cells. Conclusion The results suggest that MRE suppresses growth and inhibits epithelial-mesenchymal transition in MCF-7 cells.